Hybrid PLA-based biocomposites produced by DLP 3D printer with alumina and silica nanoparticles - Maleki, Hossein; Asadi, Parviz; Moghanian, Amirhossein; Safaee, Sirus; Najjar, I. M. R.; Fathy, A. (Elsevier, 2025)
With advancements in science and technology, biomedicine, particularly in biomedical materials, has experienced rapid growth. Achieving low toxicity and excellent biocompatibility remains critical in developing these materials. Polylactic acid (PLA) is among the most widely used materials in the biomedical sector due to its favorable processability, mechanical properties, and biocompatibility. This study investigates the mechanical properties of PLA nanocomposite samples produced using Digital Light Processing (DLP). Alumina (Al2O3) and silica (SiO2) ceramics, known for their biocompatibility and extensive use in medical devices, were incorporated to create hybrid nanocomposites. The effects of printing layer thickness (50, 75, and 100 micrometers) and reinforcement volume fraction (up to 8 wt%) on the properties of the samples were examined. The results indicated that samples with thinner layers exhibited higher strength. Raising the alumina volume fraction to 8 wt % enhanced the tensile strength and wear resistance by approximately 16 % and 62 %, respectively, compared to pure resin samples. In contrast, while the reinforcing of silica up to 2 wt% decreased tensile strength compared to pure resin, wear resistance improved by 69 %, surpassing the effects of alumina. In hybrid nanocomposites, the incorporation of silica reduced the overall strength; specifically, a nanocomposite with 0.5 wt% silica + 3.5 wt% alumina showed a 25 % decrease in tensile strength in comparison to the nanocomposite with 4 wt% alumina, although the presence of silica increased strain by 7 %. Furthermore, wear properties improved for the nanocomposite containing 1 wt% silica + 3 wt% alumina, leading to a 22 % reduction in the wear rate compared to the 4 wt% alumina nanocomposite.
Keywords: PLA; Additive manufacturing; Biocompatibility; Hybrid nanocomposite; Wear; Fracture surface